Flatness Based Sensorless Control of PMSM Using Test Current Signal Injection and Compensation for Differential Cross-Coupling Inductances at Standstill and Low Speed Range - Piepenbreier, Bernhard; Seilmeier, Markus; et al. (IEEE International Symposium on Sensorless Control for Electrical Drives and Predictive Control of Electrical Drives & Power Electronics (SLED-PRECEDE 2013), 2013)
This paper presents a novel flatness based two-degree-of-freedom (2DoF) sensorless control scheme for PMSM at standstill and for low speed range using test current signal injection in the estimated d-axis of the field oriented dq-coordinate system. Asymmetrical winding and saturation might cause the occurrence of differential cross-coupling inductances and as a result the estimated rotor position deviates from the real value. The differential cross-coupling inductances have to be compensated for to overcome this problem. For that a flatness based dynamic feed-forward control is proposed. The control error due to model uncertainties is minimized using a controller that fulfills the internal model principle. The control signal of the high frequency controller in the q-axis is demodulated and afterwards used as the input signal of a tracking-observer to estimate the rotor position. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEEAS.flatne
Keywords: Inductances; Permanent magnet machines; Sensorless control; State-space methods